2023
DOI: 10.3847/1538-4357/acb64c
|View full text |Cite
|
Sign up to set email alerts
|

BICEP/Keck. XVI. Characterizing Dust Polarization through Correlations with Neutral Hydrogen

Abstract: We characterize Galactic dust filaments by correlating BICEP/Keck and Planck data with polarization templates based on neutral hydrogen (H i) observations. Dust polarization is important for both our understanding of astrophysical processes in the interstellar medium (ISM) and the search for primordial gravitational waves in the cosmic microwave background (CMB). In the diffuse ISM, H i is strongly correlated with the dust and partly organized into filaments that are aligned with the local magnetic field. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In recent years, with the increasing availability of H I emission observations, including some largescale high-spatial resolution observational surveys, there has been growing interest in deriving the properties of the ISM from the H I spatial morphology, with fruitful results. The physics probed by the H I morphology includes H 2 formation (Barriault et al 2010), galaxy dynamics (Soler et al 2020(Soler et al , 2022, high-velocity cloud instabilities (Barger et al 2020), galactic outflows (McClure-Griffiths et al 2018;Di Teodoro et al 2020), star formation (Hacar et al 2022;Yu et al 2022), and the structure of the interstellar magnetic field, with applications to cosmological foregrounds (Clark et al 2014(Clark et al , 2015Kalberla & Kerp 2016;Clark 2018;Clark & Hensley 2019;Ade et al 2023). In particular, the study of H I intensity maps using machine vision algorithms, like the Rolling Hough Transform (RHT; Clark et al 2014), has revealed remarkably linear filamentary features that align with magnetic field directions, as traced by dust and starlight polarization (Clark et al 2014(Clark et al , 2015Kalberla & Kerp 2016;Clark & Hensley 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increasing availability of H I emission observations, including some largescale high-spatial resolution observational surveys, there has been growing interest in deriving the properties of the ISM from the H I spatial morphology, with fruitful results. The physics probed by the H I morphology includes H 2 formation (Barriault et al 2010), galaxy dynamics (Soler et al 2020(Soler et al , 2022, high-velocity cloud instabilities (Barger et al 2020), galactic outflows (McClure-Griffiths et al 2018;Di Teodoro et al 2020), star formation (Hacar et al 2022;Yu et al 2022), and the structure of the interstellar magnetic field, with applications to cosmological foregrounds (Clark et al 2014(Clark et al , 2015Kalberla & Kerp 2016;Clark 2018;Clark & Hensley 2019;Ade et al 2023). In particular, the study of H I intensity maps using machine vision algorithms, like the Rolling Hough Transform (RHT; Clark et al 2014), has revealed remarkably linear filamentary features that align with magnetic field directions, as traced by dust and starlight polarization (Clark et al 2014(Clark et al , 2015Kalberla & Kerp 2016;Clark & Hensley 2019).…”
Section: Introductionmentioning
confidence: 99%